2018
DOI: 10.1016/j.tranon.2018.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Gene Fusion in Malignant Glioma: An Emerging Target for Next-Generation Personalized Treatment

Abstract: Malignant gliomas are heterogeneous diseases in genetic basis. The development of sequencing techniques has identified many gene rearrangements encoding novel oncogenic fusions in malignant glioma to date. Understanding the gene fusions and how they regulate cellular processes in different subtypes of glioma will shed light on genomic diagnostic approaches for personalized treatment. By now, studies of gene fusions in glioma remain limited, and no medication has been approved for treating the malignancy harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 97 publications
1
35
0
Order By: Relevance
“…The various downstream signalling targets of this molecule such as PI3K/AKT have already been mentioned above. This work showed augmented levels of FGFR1 in the resistant lines that were in lieu of a recent study that showed similar up‐regulation in U87/TR cells . FGFR1 has also been shown to be oncogenic in the case of glioma by modulating the ability of cells to divide, migrate and invade .…”
Section: Discussionsupporting
confidence: 75%
“…The various downstream signalling targets of this molecule such as PI3K/AKT have already been mentioned above. This work showed augmented levels of FGFR1 in the resistant lines that were in lieu of a recent study that showed similar up‐regulation in U87/TR cells . FGFR1 has also been shown to be oncogenic in the case of glioma by modulating the ability of cells to divide, migrate and invade .…”
Section: Discussionsupporting
confidence: 75%
“…Gene fusions involving NTRK1, NTRK2 or NTRK3 (encoding TRKA, TRKB and TRKC, respectively) occur at varying frequencies in GBM, with NTRK2 fusions the most commonly observed (up to 11% of GBM). NTRK1 and NTRK3 are observed in <1% of cases, 107,108 These NTRK fusions drive ligand-independent activation of the TRK, resulting in activation of a variety of downstream cascades including RAS/RAF/MEK/ERK and PI3K/AKT pathways, ultimately promoting tumour cell proliferation and survival. 109 To date, it has been shown that overexpression of the neurofascin (NFASC)-NTRK1 fusion gene in NIH 3T3 cells increases cell proliferation, colony formation and tumour formation in a xenograft model.…”
Section: Neurotrophic Tropomyosin Receptor Kinase Fusions and Braf Almentioning
confidence: 99%
“…Oncogenic NTRK fusions with various partner genes result in chimeric receptor kinase proteins that lead to an uncontrolled activation of the tyrosine kinase signaling pathway. NTRK fusions are encountered in 2 categories of tumors; at a high frequency in some rare cancers such as secretory carcinoma of the salivary gland, secretory breast carcinoma, congenital mesoblastic nephroma, and infantile fibrosarcoma, 4‐8 and at a lower frequency in more common cancers, including thyroid cancer 9‐18 . However, NTRK fusions are found at a higher frequency in certain PTC populations, reaching as high as 26% in pediatric PTC patients and 10% to 15% in postradiation PTC patients 17,19‐22 …”
Section: Introductionmentioning
confidence: 99%